2021
DOI: 10.1111/eva.13327
|View full text |Cite|
|
Sign up to set email alerts
|

Population and seascape genomics of a critically endangered benthic elasmobranch, the blue skate Dipturus batis

Abstract: The blue skate (Dipturus batis) has a patchy distribution across the North‐East Atlantic Ocean, largely restricted to occidental seas around the British Isles following fisheries‐induced population declines and extirpations. The viability of remnant populations remains uncertain and could be impacted by continued fishing and by‐catch pressure, and the projected impacts of climate change. We genotyped 503 samples of D. batis, obtained opportunistically from the widest available geographic range, across 6 350 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 101 publications
1
14
0
Order By: Relevance
“…Little information is available about blackmouth catshark genetic diversity and population structure (Ferrari et al, 2018;Ramıŕez-Amaro et al, 2018), being the molecular method previously applied for integrated taxonomy (Castilho et al, 2007) and food traceability (Clarke et al, 2006). With the refinement of genetic and genomic techniques, deepening the knowledge about species genetic diversity and structuring is becoming one of the pillars of elasmobranchs' conservation (Ovenden et al, 2019;Domingues et al, 2021;Delaval et al, 2022). Finding population structure across wide geographical or global scales failed in pelagic sharks (Hoelzel et al, 2006;Verıśsimo et al, 2017) although some exceptions are reported (Kraft et al, 2020), while the identification of isolated populations on smaller regional scales has been documented in multiple coastal species (Portnoy et al, 2015;Catalano et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Little information is available about blackmouth catshark genetic diversity and population structure (Ferrari et al, 2018;Ramıŕez-Amaro et al, 2018), being the molecular method previously applied for integrated taxonomy (Castilho et al, 2007) and food traceability (Clarke et al, 2006). With the refinement of genetic and genomic techniques, deepening the knowledge about species genetic diversity and structuring is becoming one of the pillars of elasmobranchs' conservation (Ovenden et al, 2019;Domingues et al, 2021;Delaval et al, 2022). Finding population structure across wide geographical or global scales failed in pelagic sharks (Hoelzel et al, 2006;Verıśsimo et al, 2017) although some exceptions are reported (Kraft et al, 2020), while the identification of isolated populations on smaller regional scales has been documented in multiple coastal species (Portnoy et al, 2015;Catalano et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Due to cost considerations, we were unable to genotype all samples. Of those available, 683 were selected for genotyping, of which 387 had already been genotyped by Delaval et al ( 2022 ) using the same method. Samples primarily consisted of juveniles and young adults, but spanned as wide a size range as possible to maximize the number of cohorts included in the model.…”
Section: Methodsmentioning
confidence: 99%
“…In an effort to evaluate current management regimes, longitudinal fisheries‐dependent surveys have been initiated in collaboration with British (Bendall et al, 2018 ) and French (Barreau et al, 2016 ) fishing fleets in order to develop demographic models and identify biologically important sites for the species. Initial results from these surveys suggest the occurrence of juveniles and adults in the area, displaying a high degree of site fidelity, while population genomic analysis has identified the occurrence of siblings in the area and limited gene flow with offshore populations (Delaval et al, 2022 ). Altogether, these findings suggest that the Celtic Sea may host important reproductive and/or nursery sites for D. batis .…”
Section: Introductionmentioning
confidence: 99%
“…Herein, these processes are addressed in diverse empirical model systems ranging from diatoms to mollusks and fish (Green et al, 2022 ; Le Moan et al, 2022 ; Sefbom et al, 2022 ; Zhang et al, 2022 ), as well as in silico in two theoretical modeling studies (Eriksson et al, 2022 ; Marshall & Connallon, 2022 ). The link between genotype and phenotype is also the focus of several empirical studies here (Gefaell et al, 2022 ; Stenger et al, 2022 ; Walker et al, 2022 ), as is the seascape genomics of a wide range of taxa (Delaval, Bendall, et al, 2022 ; Delaval, Frost, et al, 2022 ; Fitz et al, 2022 ; Lapègue et al, 2022 ; Matias et al, 2022 ; Palumbi et al, 2022 ; Pampoulie et al, 2022 ), which has important implications for management of marine resources. Finally, the breadth of phylogenetic diversity and evolutionary history in the oceans is the topic of several articles focusing on the larval development of gastropods (Korshunova et al, 2022 ; Sun et al, 2022 ) and the evolution of small RNAs in cnidarians (Li & Hui, 2022 ).…”
Section: Introductionmentioning
confidence: 98%